Functional Disability After Ischemic Stroke: A Community-Based Cross-Sectional Study in Shanghai, China - Yao, Ying-Ye; Wei, Zi-Jun; Zhang, Yue-Chan; Li, Xiang; Gong, Liu; Zhou, Jia-Wei; Wang, Yu; Zhang, Yun-Yun; Wang, Rui-Ping (Frontiers in Neurology, 2021)
Abstract Objective: To understand the demographics, functional disabilities, cognitive impairment and depressive mood among stroke patients, and to explore their correlation with the degree of functional disabilities. Methods: A cross-sectional study to investigate the functional status (modified Rankin Scale, mRS) of ischemic stroke patients between 1 month–2 years after stroke. Data were collected between October 2016 and January 2017 from 11 communities in two districts of Shanghai, China. We used face-to-face questionnaire interviews to collect data on socio-demographics, vascular risks associated with stroke, cognitive function (Mini-Mental State Examination, MMSE), and depression (Patient Health Questionnaire-9, PHQ-9). Results: We recruited 305 patients with ischemic stroke, including 189 (61.97%) males, with an average age of 67 years. Patients were divided into three groups according to mRS score, including patients without symptoms (controls, mRS=0), patients without obvious disability (mRS=1), and patients with mild to severe disability (mRS=2-5). Stroke patients with different mRS levels demonstrated significant differences in age, tobacco smoke, previous stroke history, cognitive function, and depression state. Compared with controls, the correlation of patients with mRS=1 was the lower MMSE score [OR(odds ratio)=0.48, 95% CI (Confidence Interval) :0.26-0.90], while those of patients with mRS=2-5 were previous stroke history [OR=2.18, 95% CI: 1.01-4.79] and/or lower MMSE scores [OR=0.16, 95% CI: 0.08-0.33] and/or higher PHQ-9 level [OR=5.36, 95% CI: 2.19-13.11]. Conclusion: A higher degree of life dependence is related to cognitive impairment, as well as past stroke history and depression.